Mycoplasma-like diseases - Granada, G.; Kitajima, E. (International Center for Tropical Agriculture, 1989)
Since 1967, many diseases have been associated with mycoplasma- like microorganisms (MLM), especially when symptoms have been characterized by general plant chlorosis, stunting, excessive proliferation of branches (witches' broom), bud proliferation and disorders of floral organs (phyllody and virescence). Many causal agents are transmitted naturally by leafhoppers to various hosts. Various MLM are known to infect beans, such as legume little-leaf transmitted by Orosius argentatus, witches'-broom, phyllody and virescence. In Colombia, a MLM was detected and is known as machismo or amachamiento, transmitted by Scaphytopius fuliginosus. The symptoms of infection generaly become apparent during flowering and pod development. Control measures include adequate crop rotation and elimination of weed hosts, and the use of insecticides. The symptoms and damage caused by the organisms are illustrated in color. (CIAT)